Examination of A Novel Nanocompositer’s Bioactivity for Use in Dentistry - Amanolahi Baharvand , Sarvenaz; Chaboki , Pardis; Pourhatami , Fateme; Shirvandehi, Mohamad Milad; Yusofvand , Reza; Ali –Khiavi, Payam; Shabestari Khiabani , Mohammad; Yousefi , Khadije; Ganji Nataj, Paria; Arjmandi Sarvestani , Paria; et al. (Galen Medical Journal, 2024)
The extended setting time of mineral trioxide aggregate (MTA) is one of its primary drawbacks. An alternative to MTA, Nano Fast Cement (NFC) is a novel nanocomposite with a quick setting time. In order to develop an exceptional dental filler, hydroxyapatite nanoparticles (NHA) were introduced to NFC to examine its impact on setting time, biocompatibility, and bioactivity qualities. X-ray diffraction, scanning electron microscopy, Gilmore needle, and MTT assay were used to evaluate the specimens with 0, 10, and 20 W% hydroxyapatite. The antibacterial evaluation was conducted using Enterococcus faecalis (PTCC 1394). Using phase and microstructural studies, the production of hydroxyapatite was discovered. Both 10 and 20 weight percent prime apatite enhanced the specimens’ bioactivity and markedly decreased their toxicity behavior. More HA content resulted in greater bioactivity enhancement and toxicity decrease. These results suggest that the physical properties of NFC were not negatively impacted by the addition of NHA. In vitro, they enhanced the filler’s bioactivity.